Happiness and financial satisfaction in Israel: Effects of religiosity, ethnicity, and war - Bernard M. S. van Praag; Dmitri Romanov; Ada Ferrer-i-Carbonell (Center for Economic Studies and ifo Institute (CESifo), 2010)
We analyze individual satisfaction with life as a whole and satisfaction with the personal financial situation for Israeli citizens of Jewish and Arab descent. Our data set is the Israeli Social Survey (2006). We are especially interested in the impact of the religions Judaism, Islam and Christianity, where we are able to differentiate between individuals who vary in religiosity between secular and ultra-orthodox. We find a significant effect of religiosity on happiness. With respect to Jewish families it is most striking that the impact of family size on both life and financial satisfaction seems to vary with religiosity. This might be a reason for differentiation in family equivalence scales. For Arab families we did not find this effect. First-generation immigrants are less happy than second-generation immigrants, while there is no significant difference between second-generation families and native families. The effect of the Lebanon War is much less than expected.
Keywords: H56; I31; N35; N45; R23; Z12; 330; happiness; subjective well-being; financial satisfaction; Israel; religion; immigration; terrorism; Zufriedenheit; Lebensqualität; Soziale Lage; Judentum; Politische Gewalt; Israel